Epidemiologic trends and characteristics of cancer-related emergency department visits of older patients living with cancer in South Korea - Jung-In Ko; Sun Young Lee; Shin Hye Yoo; Kyae Hyung Kim; Belong Cho (Scientific Reports)
Abstract We aimed to investigate the demographic characteristics, common chief complaints, and diagnosis of geriatric cancer-related emergency department (ED) visits and trends of ED outcomes. This retrospective observational study included all ED visits in South Korea between 2016 and 2020. The study population was older people ≥ 65 years living with cancer who visited ED with cancer-related problems. The demographics, common diagnoses, and ED outcomes were investigated. A multivariate logistic regression analysis was conducted to investigate factors associated with mortality. Geriatric cancer-related ED (GCED) visits were 746,416 cases over 5 years. The proportion of older adults among cancer-related ED visits increased from 50.1% in 2016 to 55.3% in 2020. The proportion of the “oldest old” (≥ 85 years) increased from 9.6 to 12.1%. For GCED, the ward admission rate after ED treatment was 60.2% and in-hospital mortality rate was 11.8%. Both of these increased with age group (“young old” (65–74), “middle old” (75–84), and “oldest old” (≥ 85 years) groups admission rates: 56.1%, 62.8%, and 68.0%; and mortality rates: 10.0%, 12.7%, and 15.7%, respectively). The most common diagnosis was pneumonia (4.9%). Old age and ambulance use were also associated with mortality. Older adults account for more than half of cancer-related ED visits, and their number is increasing every year. GCED visits are associated with high hospitalization and mortality, especially among the oldest old. It is important to prepare for a rise in GCED visits is necessary.